Accounting of Biological Assets in Indonesian Plantation Companies - Baroroh, N; Yanto, H; Fajarrini, I; Agustina, L (KnE Social Sciences, 2018)
The purpose of this study is to analyse the recognition, measurement, disclosure and presentation of biological assets in Indonesian plantation companies. The population of this study is all plantation companies registered in Indonesia Stock Exchange which amounts to 12 companies. This study involved the entire population as a sample. Further, this study uses descriptive-qualitative method through secondary data in the form of company financial report. The results of the study present that Indonesian plantation companies comply with PSAK (Indonesian Accounting Standards) in the application of biological asset records. The biological assets were measured at the acquisition cost by accumulating all expenditures from planting until the assets were ready to produce and were presented in the report of financial position with the classification of yielding and not yet yielding crops. The biological assets were depreciated on a straight-line method with an average economic life of 20-25 years. Keywords: Biological assets, accounting, Indonesia, yielding crop